Exchange rates, employment and labour market rigidity - Alexandre, Fernando (2017)
In this paper, we study the effect of labour market rigidity on the impact of exchange rate shocks on employment. We use a panel dataset comprising 22 manufacturing sectors across 23 OECD countries. In our econometric model, the impact of exchange rate fluctuations on sectoral employment is mediated by the degree of openness and by a measure of labour market rigidity: the OECD's employment protection legislation (EPL) index. Our results suggest that greater labour market rigidity reduces the impact of exchange rate shocks on employment. This effect is statistically significant for low-technology sectors.